2012
DOI: 10.4236/wjnse.2012.22013
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in Mechanical Properties of Polystyrene Filled with Carbon Nano-Particulates (CNP<sub>S</sub>)

Abstract: The idea of adding reinforcing materials, or fillers, to polymers has been around for many decades. The reason for the creation of polymer composite materials came about due of the need for materials with specific properties for specific applications. For example, composite materials are unique in their ability to allow brittle and ductile materials to become softer and stronger. It is expected that good tribological properties can be obtained for polymers filled with nano-scale fillers. A soft plastic can bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…PS being cost-effective commercial commodity plastic material has been utilized as one of the important polymeric materials for various NLO-active devices (Sureshkumar et al 2008). It is reported that the optical properties, magnetic properties, and mechanical properties of PS were significantly improved after embedding metal or semiconductor nanoparticles into the polymer matrix (Nikkeshi et al 1998;Zhu and Schmauder 2003;Ahmad and Mamat 2011;Aly et al 2012;Sangawar and Golchha 2013). It is reported that addition of metal nanoparticles can enhance the thermal conductivity and heat transfer of fluid (Sheikholeslami 2017a, b;Sheikholeslami and Vajravelu 2017).…”
Section: Introductionmentioning
confidence: 99%
“…PS being cost-effective commercial commodity plastic material has been utilized as one of the important polymeric materials for various NLO-active devices (Sureshkumar et al 2008). It is reported that the optical properties, magnetic properties, and mechanical properties of PS were significantly improved after embedding metal or semiconductor nanoparticles into the polymer matrix (Nikkeshi et al 1998;Zhu and Schmauder 2003;Ahmad and Mamat 2011;Aly et al 2012;Sangawar and Golchha 2013). It is reported that addition of metal nanoparticles can enhance the thermal conductivity and heat transfer of fluid (Sheikholeslami 2017a, b;Sheikholeslami and Vajravelu 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The ultrathin dielectric quality could be improved by the introduction of the sputtered C NPs, since it has been reported that the addition of C can enhance the mechanical and insulating properties of low-k polymers. [ 31,32 ] In the present case, because of the expected strong interaction between the C NPs and the polymers, the adhesion of the polymer dielectrics on the substrate is greatly reinforced. Therefore, the PS/C, PMMA/C, and PVN/C dielectrics can be robust and free of tiny pinholes and cracks.…”
Section: Doi: 101002/aelm201500349mentioning
confidence: 88%
“…From the concept of hardness, it can be considered as plastic deformation measure where a material can suffer under impact of the external stresses. Thus, the addition of reinforcing material to base material results in increasing the material hardness as a result of increasing its resistance to plastic deformation [8], as well as the penetration of the reinforcing material into the base material within the interspaces and vacancies results in an increase in contact area and therefore a link between the base material and the reinforcing material, which leads to strengthening of the composite and after that, an increase in hardness [9]. Table (2) illustrates hardness values of all of the polymeric blend films.…”
Section: Mechanical Characteristicsmentioning
confidence: 99%